THE SUBTITLE STRATEGY OF SLANG TRANSLATION IN 21 JUMP STREET MOVIE FAN SUBTITLES - Mar'i Muhammad Bima Saputra (CrossOver, 2021)
Abstract Slang is one of the aspects of languages that requires experience and knowledge. Some of the slang is not only for delivering certain meaning but also for identifying or expressing the speaker. Slang also appears in the subtitles of the film. Related to this case, this research aims (1) to describe types of slang that is found in 21 Jump Street movie by Original Film, (2) to describe what subtitle strategies that the subtitler used to translate the slang in 21 Jump Street movie by Original Film, and (3) to describe the relationship between the most widely used subtitling strategies and the type of slang that dominantly appears in 21 Jump Street movie. This research is descriptive qualitative research and the expert is involved in the case to validate the data analysis. There were 145 data collected. 21 data are categorized as "Group- and subject-restriction", 2 data as "Secrecy and Privacy", 67 data as "Informality and Debasement", and 55 data as "Vulgarity and Obscenity." The most common category is the "Informality and Debasement" category. On the second analysis, of these 145 data, the strategy mostly used by the subtitler or translator is the "paraphrase" strategy with a total of 57 data. The type of slang that is mostly found which is "Informality and Debasement" is most dominantly translated using the "paraphrase" strategy. This suggests that slang representing intimacy and informality cannot be translated into the same form and way as the source language. The informality here can mean that the characters in this film see the people around them as close people or even to make strangers closer. The strategy used also influences the meaning contained. Some of them need to be translated not synthetically in order to convey the meaning of the slang.